Challenges of Korean Immigrant Leadership in the Church - Choi, Hee An (International journal of practical theology, 2019)
The article suggests that the practices of leadership within Korean communal transformational leadership in Korean resistance movements provide a resource for women in the Korean immigrant church. The article addresses the challenges of Korean leadership in immigrant contexts, how immigrant leadership is performed and transformed, and how immigrants have developed and adapted their leadership from a Korean to US context during the immigrant identity transformation process.